Hubungan tingkat pengetahuan orang tua tentang kesehatan gigi dengan terjadinya karies pada anak prasekolah di TK Aisyiyah Bustanul Athfal - Fadlilah, Siti (Journal of Oral Health Care, 2019)
Preschool children are a period of growth for children. Dental caries is often observed among preschool children. The Basic Health Research reports that the prevalence rate of caries in Indonesia reaches 25.9%. This condition is very saddening because preschool-children need their parents to take care of their health, particularly dental health. In this case, parents’ knowledge is very much needed in providing more guidance and care in order that the children do not have dental caries. To was aimed at identifying the correlation between parents’ knowledge of dental health with the prevalence of dental caries among preschool children at Aisyiyah Bustanul Athfal Nursery School, Wedomartani, Ngemplak, Sleman, Yogyakarta. This research was a correlation analysis with a cross-sectional design. The subjects were parents, particularly mothers, whose children studied at Aisyiyah Bustanul Athfal Nursery School. It was a simple random sampling technique with 64 respondents. The data collection instrument consisted of a questionnaire and an observation sheet. The data were analyzed with the Spearman Rank statistics. This research found that the knowledge of dental health of 50.0% of the parents was categorized as good, the dental caries prevalence of the children were 71,9%. The research hypothesis was accepted with a p-value of 0.023 and the correlation coefficient was 0.285. There was a significant correlation between the parents’ knowledge of dental health with the prevalence of dental caries among preschool children at Aisyiyah Bustanul Athfal Nursery School, Wedomartani, Ngemplak, Sleman, Yogyakarta.